Continued professor training and inclusive education: the knowledge teachers in dialogue with the university extension - Martins, Elita Betânia de Andrade; Antunes, Katiuscia C. Vargas; Monteiro, Sandrelena da Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
Thinking about teachers formation processes is a real challenge to be faced by institutions. This article presents the experience of a partnership between two research groups of a Faculty of education that have joined efforts, after the professors realized the challenges faced by the lack of knowledge of both students and school teachers, concerning education of people with special needs. It was therefore proposed an university extension programme, which consisted of a cooperative learning proposal and a colective learning-teaching study method, consisting of group talks. It is a given fact that institutions of basic education face a real challenge, concerning an inclusive education. But it is also a fact that, when we consider that continued education is also responsability of these institutions, the space time frames of university extension could and should consist of a laboratory in which we should learn to cooperate, learn to be in cooperation and learn how cooperative education can teach us another way of being in the world.